2019
DOI: 10.1371/journal.pone.0203248
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit learning in reactive and voluntary saccade adaptation

Abstract: Saccades can either be elicited automatically by salient peripheral stimuli or can additionally depend on explicit cognitive goals. Similarly, it is thought that motor adaptation is driven by the combination of a more automatic, implicit process and a more explicit, cognitive process. However, the degree to which such implicit and explicit learning contribute to the adaptation of more reactive and voluntary saccades remains elusive. To study this question, we employed a global saccadic adaptation paradigm with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…An established convention of motor learning asserts that automatic or implicit components of learning emerge later in training following an initial more explicit or declarative stage, even for skill-maintenance tasks, like adaptation 1 6 . Perturbations in reach, saccade and locomotion adaptation evoke relatively quick adjustments to behaviour 4 , 6 12 , and some work has attempted to either infer implicit learning based on the assumption that implicit and explicit adaptation simply add to produce behavior 13 or measure it in paradigms that require explicitly suppressing natural responses to visual feedback 11 , 12 . However, it has not been directly measured how quickly implicit changes emerge.…”
Section: Introductionmentioning
confidence: 99%
“…An established convention of motor learning asserts that automatic or implicit components of learning emerge later in training following an initial more explicit or declarative stage, even for skill-maintenance tasks, like adaptation 1 6 . Perturbations in reach, saccade and locomotion adaptation evoke relatively quick adjustments to behaviour 4 , 6 12 , and some work has attempted to either infer implicit learning based on the assumption that implicit and explicit adaptation simply add to produce behavior 13 or measure it in paradigms that require explicitly suppressing natural responses to visual feedback 11 , 12 . However, it has not been directly measured how quickly implicit changes emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Two main implicit changes involved in adaptation, that rely on sensory-prediction error-based learning, are updates in internal models as well as the resulting changes in our state estimates (6)(7)(8). While perturbations in reach, saccade and locomotion adaptation evoke relatively quick adjustments to behaviour (4,(9)(10)(11)(12), it has not been directly measured how quickly implicit changes emerge.…”
Section: Introductionmentioning
confidence: 99%
“…An established convention of motor learning asserts that automatic or implicit components of learning emerge later in training following an initial more explicit or declarative stage, even for skillmaintenance tasks, like adaptation [1][2][3][4][5][6] . Perturbations in reach, saccade and locomotion adaptation evoke relatively quick adjustments to behaviour 4,[6][7][8][9][10][11][12] , and some work has attempted to either infer implicit learning based on the assumption that implicit and explicit adaptation simply add to produce behavior 13 or measure it in paradigms that require explicitly suppressing natural responses to visual feedback 11,12 . However, it has not been directly measured how quickly implicit changes emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Though sensorimotor adaptation was traditionally viewed as a testbed for examining procedural learning, recent studies have shown that various adaptation paradigms involve both explicit and implicit learning. Besides the visuomotor rotation investigated here, reaching adaptation with force field [ 52 ] or prism goggles [ 53 ], walking adaptation with a split-belt [ 54 ], and saccadic adaptation with a target jump [ 55 ] all involve cognitive components and strategic corrections to the perturbation. Taking force field adaptation as an example, people rely on proprioceptive feedback to adapt to a novel mechanical environment and have difficulty verbalizing their adaptation solution.…”
Section: Discussionmentioning
confidence: 99%